Educação e informação em contexto de políticas públicas pesquisas em foco - Fujita, Mariângela Spoti Lopes (Editora Oficina Universitária, 2023)
It is with immense satisfaction that we present the book to readers, as it is the result of an important agreement signed between the Municipal Secretary of Education (SME) of the municipality of Marília/SP and the São Paulo State University (UNESP), especially represented by the Graduate Programs in Education and Information Sciences (PPGE and PPGCI) of the Faculty of Philosophy and Sciences (FFC), Campus Marília. The agreement signed between the SME of the municipality of Marília and Unesp opened a long-awaited opportunity for education professionals from the municipal network of Marília to have an exclusive public notice dedicated to their scientific training at the master's and doctoral level. This opportunity was an open window from monthly meetings held by researchers from the Institute of Public Policies of Marília (IPPMar) with SME administration and professors from February to September 2017, which aimed to carry out an active interaction between IPPMar and municipal public management and, at that time, the Municipal Secretary of Education showed great interest and participation.